Differentiation strategy: an easy way to make your business stand out in the market - Suharto, Suharto (Journal of Economics and Business (JECOMBI), 2024)
In the context of increasingly fierce competition, companies are faced with the challenge of differentiating themselves from similar competitors. Differentiation strategy is considered an approach that can increase business attractiveness and create added value for customers. This research aims to investigate and analyze differentiation strategies as an effective method for making a business stand out in the market. This research uses a qualitative approach with descriptive methods. The results of this research show that a differentiation strategy, with a focus on product innovation, maintained quality, honest offers, and understanding consumer perceptions, is able to create significant added value. Innovation not only creates differences, but also provides solutions that are relevant to consumer needs, while product quality and honest offers are the basis for consumer trust. Deep understanding of consumer perceptions through smart promotions forms a strong emotional bond between consumers and products. Overall, differentiation strategy is the key to success in making a business stand out in a competitive market.